Pengaruh Karakteristik Demografi, Dimensi Keterlibatan konsumen, dan Pengenalan Kebutuhan Terhadap Keputusan Pembelian Mobil Avanza - Samoel, Philip; Marpaung, Bintang Sahala (Jurnal Ilmiah Manajemen Kesatuan, 2019)
Based on the research, it is concluded that there is one factor that has a positive and significant effect on the purchase decision variable. The factor is the Consumer Involvement Dimension variable (X2). With the acquisition of t-count is greater than t - table that is equal to 6.012> 1.660. Then through the F test indicates that there is a positive and significant influence on the purchasing decision with the acquisition of a bigger f - count than the f - table of (83.865> 3.783). With r square value equal to 72,4% which means independent variable of demography characteristic, consumer engagement dimension, and purchasing decision have positive effect, meaning every increase of demographic characteristic variable, dimension of consumer involvement, and purchasing decision one-unit hence variable purchase decision will increased by 3,009 and the rest of 27,6% influenced by other variable not examined in this research